ChatGPT and higher education assessments: More opportunities than concerns? (Journal of Applied Learning and Teaching, 2023)
In recent times, higher education has seen a growing concern regarding the utilisation of artificial intelligence, especially with the emergence of ChatGPT. This technology can generate written content and respond to queries at a level that is nearly indistinguishable from a human writer. This feature has drawn substantial interest from students in higher education and has led to concern that students will use ChatGPT’s capabilities to cheat on written formative and summative assessments. In this paper, we will review the usage of ChatGPT in higher education assessments and investigate why students want to cheat using artificial intelligence capabilities. It also offers a critical perspective on the challenges associated with detecting ChatGPT-generated content and its impact on academic integrity. We also consider whether artificial intelligence provides more opportunities for academics to focus on assessing higher-order thinking and strategies.